Transcriptome and DNA methylation analyses provide insight into the heterosis of growth-related traits in hybrid yellow croaker - Dan-Dan Guo; Feng Liu; Qing-Ping Xie; Ting Ye; Fu-Liang Wei; Bao-Long Niu; Bao Lou (BMC Genomics)
Abstract Background Interspecific hybrid combinations of Larimichthys crocea × Larimichthys polyactis exhibit heterosis in terms of growth traits; however, the molecular regulatory mechanism underlying this phenomenon remains unclear. DNA methylation plays a pivotal role in regulating gene expression and is involved in growth and development processes. In this study, we comprehensively investigated intricate regulatory processes by integrating transcriptome and methylome datasets from brain, liver, and muscle tissues. Results We analyzed a total of 72 sequence datasets, including transcriptome and genome-wide DNA methylome data, from 36 tissue samples using LC, LP, LPC and LCP. We elucidated the distinct expression patterns of these four populations and examined their interactions with DNA methylation. Our findings revealed diverse DNA methylation profiles and demonstrated a greater number of hypo-DMRs in hybrid yellow croakers than in their parental lines. The majority (86 ~ 92%) of these DMRs were observed within the CG context. Moreover, we found that most DMRs were located within promoter regions as well as exons and introns. A total of 1288 DMEGs were identified through correlation analysis between DNA methylation and transcriptional activity. Functional enrichment analysis revealed that most of the DMEGs were significantly enriched in pathways related to the protein export pathway, proteasome, terpenoid backbone biosynthesis, ubiquitin-mediated proteolysis, autophagy-other pathway. Furthermore, we screened candidate growth-related genes, such as stat2, capn2, akt1, mTOR, and mef2aa. Among these, the expression levels of capn2, mTOR, and akt1 exhibited a positive correlation with DNA methylation levels, whereas the expression levels of stat2 and mef2aa showed a negative correlation. These findings suggest that alterations in DNA methylation patterns may promote growth advantages in hybrid yellow croaker by modulating the expression of these genes. Conclusions Epigenetic changes exert distinct influences on genes related to growth heterosis. The presented data establish a foundation for comprehending the epigenetic and transcriptomic alterations underlying the growth of hybrid yellow croaker, thereby providing preliminary insights into the molecular mechanisms of growth heterosis. These findings have significant implications for breeding programs aimed at enhancing yellow croaker production.